The Acoustic Transparency of Waterproof Smartphone Cases - Fray, Sarah M.; Thibodeau, Linda M. (Seminars in Hearing, 2020)
Phone use is a critical communication event in many people's lives. Audiologists have aimed to assist individuals with hearing loss and phone usage through the use of technology and counseling. To counsel effectively, all contributions to hearing difficulty on the phone must be considered, including the effects of smartphone cases. The purpose of this study was to evaluate the effects on dB output caused by waterproof smartphone cases that cover the ear-level speaker. One waterproof case was tested with three smartphones, two iPhones, and one Android. A second waterproof case was tested with the two iPhones. Results revealed there was significant attenuation of the audio-signal by both waterproof smartphone cases that was great enough in one case/phone combination to potentially result in a complete lack of intelligibility of the signal.
Keywords: smartphone; speech intelligibility; hearing loss